The Influence Of The Contextual Learning Model And Ecoliteration On Learning Outcomes In The Natural And Social Sciences - Utami, Yolanda Adelia; Rumanta, Maman; Yani, Ahmad (Elementary Teacher Education Program, Majalengka University, 2024)
Education plays an important role in shaping the character and ability of the younger generation to face the challenges of the Times. The era of globalization, not only focuses on mastering science, but also on developing critical thinking skills and adaptability to change. The purpose of the study was to analyze and evaluate the influence of contextual learning models with ecoliteration on student learning outcomes in natural and social sciences subjects. The research method used experiments with Pre-experimental one group Pretest Posttest Design. The sample was 32 students of Grade 5 Elementary School Pulogebang 11. Data analysis using quantitative and qualitative approaches. Quantitative analysis using SPSS software version 23 and T-test (t-test). Qualitative analysis using interviews and observations. The results showed a significant increase between the pretest and posttest scores, with an average pretest of 60.81 and posttest of 84.69 with an average difference of 23.88. A significance value of 0.000, indicating a positive effect of the intervention. Hasıl interviews with teachers and students showed high student involvement, with many active and enthusiastic participants. Observations also confirm that the majority of students are actively involved in learning. In conclusion, effective learning models can create an interactive and engaging learning environment. Further research is expected to develop a more flexible learning model so that meaningful, sustainable, and adaptive learning objectives are achieved in science and social studies subjects.